Flexible Inflation Targeting and Financial Stability: Is It Enough to Stabilise Inflation and Output? - Q. Farooq Akram; Øyvind Eitrheim (Norges Bank, 2006)
We investigate empirically whether a central bank can promote financial stability by stabilizing inflation and output, and whether additional stabilization of asset prices and credit growth would enhance financial stability in particular. We employ an econometric model of the Norwegian economy to investigate the performance of simple interest rate rules that allow a response to asset prices and credit growth, in addition to inflation and output. We find that output stabilization tends to improve financial stability. Additional stabilization of house prices, equity prices and/or credit growth enhances stability in both inflation and output, but has mixed effects on financial stability. In general, financial stability as measured by e.g. asset price volatility improves, while financial stability measured by indicators that depend directly on interest rates deteriorates, mainly because of higher interest rate volatility owing to a more active monetary policy.
hdl:11250/2498368
Keywords: C51; C52; C53; E47; E52; 330; monetary policy; financial stability; asset prices; interest rate rules